2017
DOI: 10.1186/s13148-017-0389-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation analysis in blood cells from patients with Werner syndrome

Abstract: BackgroundWerner syndrome is a progeroid disorder characterized by premature age-related phenotypes. Although it is well established that autosomal recessive mutations in the WRN gene is responsible for Werner syndrome, the molecular alterations that lead to disease phenotype remain still unidentified.ResultsTo address whether epigenetic changes can be associated with Werner syndrome phenotype, we analysed genome-wide DNA methylation profile using the Infinium MethylationEPIC BeadChip in the whole blood from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…The samples with WRN and LMNA mutations clustered together and were distinct from nonmutant patients and controls. A conceptually related study (Guastafierro et al, ) found profound blood methylation differences between three classical WS patients and controls; however, these results were not statistically significant. We now report a more comprehensive methylome analysis of 24 independent patients with segmental progeria (18 with WRN , 3 with LMNA , and three with POLD1 mutations) together with carefully matched controls.…”
Section: Introductionmentioning
confidence: 83%
“…The samples with WRN and LMNA mutations clustered together and were distinct from nonmutant patients and controls. A conceptually related study (Guastafierro et al, ) found profound blood methylation differences between three classical WS patients and controls; however, these results were not statistically significant. We now report a more comprehensive methylome analysis of 24 independent patients with segmental progeria (18 with WRN , 3 with LMNA , and three with POLD1 mutations) together with carefully matched controls.…”
Section: Introductionmentioning
confidence: 83%
“…It is also possible that HES5 might be an upstream regulator of PRDM8. Aberrant hypermethylation of PRDM8 is observed in dyskeratosis congenital, aplastic anemia, Down syndrome, and Werner syndrome . PRDM8 has hypomethylated CpG islands in endometrial cancer .…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing genome-wide DNA methylation profiles of the whole blood from 3 patients with Werner syndrome and 3 age-and sex-matched healthy individuals, hypermethylated sites were enriched for genes involved in glycosphingolipid biosynthesis, FoxO signaling, and insulin signaling pathways, while hypomethylated sites were enriched in PI3K-Akt signaling and focal adhesion pathways [Guastafierro et al, 2017]. Out of 47 differentially methylated genes, 22, belonging to the enriched biochemical pathways, were differentially expressed in Werner syndrome fibroblasts.…”
mentioning
confidence: 99%
“…Although systemic sclerosis and dyskeratosis congenita are distinct from the skin lesions in patients with Werner syndrome, the altered methylation patterns of the ITGA9 and ADAM12 genes are intriguing and suggest a link between systemic sclerosis and Werner syndrome. Both the studies of Maierhofer et al [2017] and Guastafierro et al [2017] indicate a novel approach to the pathology of Werner syndrome and general ageing. Further research is needed to elucidate as to how precisely epigenetic changes and possibly altered gene expression patterns in somatic cells may contribute to stochastic age-related pathology in humans in general.…”
mentioning
confidence: 99%
See 1 more Smart Citation